Gestión Institucional y Relaciones Comunitarias en la Institución Educativa N° 65263 "Francisco Odicio Roman", Pucallpa Ucayali, 2022 - Sanchez Del Aguila, Luis Alberto (2024)
Mas info repositorio@unu.edu.pe